0 like 0 dislike
35 views
Solve for $x$ in the exponential equation $3^{2x-1}=27^{2x-1}$
in Grade 12 Maths by Bronze Status (5.9k points) | 35 views

3 Answers

2 like 0 dislike
$3 frac 2x -1 = 27 frac 2x-1$

$3 frac 2x -1 = (3 frac 3) frac 2x -1 $

$2x - 1 = 6x - 3 $

$-4x = - 2 $

$x = 1/2$
by (63 points)
edited by
0 like 0 dislike
3^(2x -1) = 27^(2x -1)

solve for x:

2x - 1 = 0

2x = 1

x = 1/2

check:

3^[2(1/2) - 1] = 27^[2(1/2) -1]

0 = 0
by Wooden (1.5k points)
0 like 0 dislike
3^2x-1= 3^6x-3

2x-1=6x-3

4x=2

x=0.5
by Bronze Status (5.8k points)

Related questions

0 like 0 dislike
1 answer
0 like 0 dislike
2 answers
asked Mar 5 in Grade 12 Maths by adminTedsf Bronze Status (5.9k points) | 28 views
0 like 0 dislike
1 answer
Welcome to MathsGee Open Question and Answer Bank, a platform, where you can ask Maths and Science questions and receive answers from other members of the community. Help is always 100% FREE!
MathsGee QnA is the knowledge-sharing community where millions of students and experts put their heads together to crack their toughest homework questions.

Enter your email address: